2018
DOI: 10.1002/slct.201800655
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted‐Acid‐Catalyzed para‐Selective Diazotization of Anilines with Aryl Diazonium Tetrafluoroborates

Abstract: An efficient brønsted acid‐catalyzed method for the para‐selective diazotization at the aromatic carbon‐hydrogen sites para to an amido substituent in nonpolar solvent is illustrated, using aryl diazonium tetrafluoroborates as diazotization reagents. The direct transformation occurs under mild reaction conditions with ample scope, avoids the use of metals, and is tolerated with valuable functional groups. It is a simple way to generate a broad spectrum of functionalized azo anilines from basic starting materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In consideration that hexahydrojulolidine constitutes the core structure of numerous bioactive Lycopodium alkaloids, we can synthesize a relevant product 7aa via full hydrogenation of the aryl ring of 3aa in the presence of 15 mol % Rh/C in i -propanol solution (Scheme d). Noteworthily, 1,2-diaryldiazenes are frequently utilized as laboratory indicators and dyes including biological stains . Here, by treating 3aa and 4-methoxyaryldiazonium tetrafluoroborate in DCE solution with diphenyl phosphonic acid catalyst, we efficiently prepared a yellow dye 8aa at room temperature (Scheme e).…”
Section: Resultsmentioning
confidence: 99%
“…In consideration that hexahydrojulolidine constitutes the core structure of numerous bioactive Lycopodium alkaloids, we can synthesize a relevant product 7aa via full hydrogenation of the aryl ring of 3aa in the presence of 15 mol % Rh/C in i -propanol solution (Scheme d). Noteworthily, 1,2-diaryldiazenes are frequently utilized as laboratory indicators and dyes including biological stains . Here, by treating 3aa and 4-methoxyaryldiazonium tetrafluoroborate in DCE solution with diphenyl phosphonic acid catalyst, we efficiently prepared a yellow dye 8aa at room temperature (Scheme e).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is not surprising that the synthesis and functionalization of imidazoheteroarenes have received considerable attention in different areas of scientific research . Analogously, arylazo compounds are widely used in several areas, including the chemical industry, pharmaceuticals, chemosensors, electronics, and liquid crystals ( 1 a – d , Figure ) . In this way, very recently, Feringa described the photoisomerization and biological evaluation of a diazo‐based privileged series of novel photoswitchable quorum‐sensing agonists and antagonists …”
Section: Figurementioning
confidence: 99%
“…The development of new synthetic procedures to obtain multitargeted hybrids of these skeletons (arylazo imidazoheteroarenes) in a single structure would be useful, due to their diverse applications ( 1 e , f , Figure ) . Although, there are several reports on the preparation of arylazo compounds, most of the protocols often suffer from acidic reaction conditions, long reaction times, low temperatures, inert atmospheres, low yields and reduced stability of the diazonium salts at room temperature . The majority of these methods proceed through strong acidic conditions, which limits their use in complex synthesis, especially when the substrates contain an acid‐labile group.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that they are effective as anti-proliferation agents in lung cancer and as antibacterials and carbonic anhydrase inhibitors. 3,9 Following our recent report of the synthesis of an azo-linked bischalcone with a sulfonamide 10 and a quinoline 11 and considering the pharmacological importance of both bischalcones and azo compounds, we set out to synthesize a new series of bischalcones possessing different…”
Section: Introductionmentioning
confidence: 99%